Divine Doppelgängers YHWH's ancient look-alikes - Cornell, Collin 1988- (University Park Penn State University Press, 2020)
Intro -- COVER Front -- Copyright Page -- Table of Contents -- Acknowledgments -- Chapter 1: God and the Gods: History of Religion as an Approach and Context for Bible and Theology -- Chapter 2: Canaan-Israel-Christianity: The Case for a Vertical Ecumenism -- Chapter 3: More Than One God? Three Models for Construing the Relations Between yhwh and the Other Gods -- Chapter 4: Who Is Like You Among the Gods? Some Observations on Configuring Yh wh in the Old Testament -- Chapter 5: Why Should the Look- Alikes Be a Problem? -- Chapter 6: Theological Approaches to the Problem of God's Ancient Look- Alikes -- Chapter 7: Chemosh Looks Like yhwh, but That's Okay -- Chapter 8: Yh wh and Chemosh: An Investigation of Look-Alike Gods Using the Moral Foundations Theory -- Chapter 9: Yh wh, Chemosh, and the Rule of Faith -- Chapter 10: Is There a Counterpart in the Hebrew Bible to New Testament Anti- Semitism? -- Chapter 11: Miqreh and Yh wh: Fate, Chance, Simultaneity,and Providence -- Chapter 12: Can a Woman Forget Her Nursing Child? "Divine Breastfeeding and the God of Israel -- Chapter 13: Bulls and Horses, Gods and Goddesses: The Religious Iconography of Israel's Neighbors -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Aufsatzsammlung